Indigenous pig management practices in rural villages of Western Kenya - Mutua, Florence K.; Dewey, Catherine E.; Arimi, S.M.; Ogara, W.O.; Githigia, S.M.; Levy, M.; Schelling, E. (2011)
The management of indigenous pigs in rural villages of Busia and Kakamega district, Western Kenya, is discussed. Data on husbandry practices, challenges and farmers knowledge on T. solium taeniosis / cysticercosis were gathered using questionnaires administered in face-to-face interviews. Pigs were examined for cysticercosis using the lingual palpation method. Data were managed in Stata®. Majority of the farmers were aged 30-50 years (44%), and were mostly women (69%). Years of pig keeping experience was higher in Kakamega (11.4±8.7) than it was in Busia (6.3±5.6) (P<0.05). Pork (31%) and beef (51%) were the most preferred meat types in the villages. Families owned an average of 0.94±0.81 hectares of land. The mean number of pigs owned per farm was 5.0 (±3.4), 1.8 (±1.2) and 1.5 (±0.9) for the pre-weaned, growing and adult pig categories, respectively. Constraints faced by the farmers included feeding (65%), diseases (46%), fewer breeding boars (60 %), poor profits (61%) and conflicts with neighbours (53%). Parasite control was poor. The majority of farmers (73%) had no pig house. These farmers either lacked skills to build the houses (11%; 23/209) or had no money to purchase construction materials (45%; 93/209). Tethering of pigs was frequent (>50%) during the planting (91%; 263 / 290), growing (90%; 263 / 290) and crop harvesting seasons (78%; 227 / 290). Prevalence of pig cysticercosis was 4.5%. Piglets were significantly cheaper in Busia (Ksh 509±57) than in Kakamega (Ksh 777±174) (P<0.05). Indigenous pig management in Western Kenya is reportedly poor. Improved knowledge coupled with changes in local husbandry practices would improve productivity, increase family incomes and safeguard the community from potential health risks associated with pig rearing.